PENYELESAIAN SENGKETA MELALUI MEDIASI DALAM KASUS PERTANAHAN - ,, Dwikornida (Normative Jurnal Ilmiah Hukum, 2022)
Mediation as regulated in Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Settlement can be used to settle land disputes, with 3 stages of the mediation process, namely the preparation stage, the stage of mediation meetings and the post-mediation stage. The legal power of resolving land disputes by mediation can be executed because if the land dispute already has a certificate because the eagle symbol is as powerful as the irah-irah for the sake of justice based on God Almighty volunteer